Tinjauan Hukum Pidana Islam atas Penerapan Justice Collaborator pada Kasus Pembunuhan Berencana UU Saksi Korban No.31/2014 - Raihan, Muhammad Sultan; Azazy, Yusup; Sumardi, Didi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This article examines the application of justice collaborator in premeditated murder cases based on Law No. 31 of 2014 concerning Protection of Witnesses and Victims, reviewed from the perspective of national law and Islamic criminal law. The focus is on finding the right legal basis for enforcing justice collaborator status for non-primary perpetrators in this crime. In Islam, this concept is not explicitly explained, so this article aims to open up new understandings regarding the possibility of its application by adjusting the principles of sharia. The research uses a normative juridical method with an approach to legislation and Islamic legal literature, such as the Qur'an, Hadith, and fiqh books. Data were collected through literature studies that include laws, court decisions, and the views of scholars. In positive law, justice collaborators are entitled to legal protection and leniency if they meet the requirements, with support from LPSK. Meanwhile, in Islamic law, if their testimony is valid and useful for resolving the case, the perpetrator can receive a reduced sentence from qishas to diyat or takzir, depending on the agreement of the victim and the authorities.